3D-printed cholecystectomy model for robotic surgery training (Transactions on Additive Manufacturing Meets Medicine, 2024)
To train surgeons in using robot-assisted surgery (RAS) systems, synthetic organ models can be used in lieu of cadavers or animal models. We have developed a 3D-printed organ model system to train operators in performing a cholecystectomy, an operation to remove the gallbladder, on RAS systems.
Keywords: 3D printing; Medical Simulation; robot-assisted surgery; robotics; cholecystectomy; planning- and educational models